Quantitative proteomic analysis of the microbial degradation of 3-aminobenzoic acid by Comamonas sp. QT12 - Zhao, Shuxue; Pan, Chao; Zhao, Junxing; Du, Haiyan; Li, Min; Yu, Hao; Chen, Xi (Scientific reports, 2022)
A mab cluster associated with 3-aminobenzoic acid (3AB) degradation was identified in Comamonas sp. QT12. However, the cellular response of Comamonas sp. QT12 to 3-aminobenzoic acid remains unclear. In this study, label-free quantitative proteome analysis based on LC–MS/MS was used to study the protein expression difference of strain QT12 under the condition of using 3AB (3AB) and citric acid/ammonium chloride as substrates (3ABCon). A total of 2068 proteins were identified, of which 239 were significantly up-regulated in 3AB group, 124 were significantly down-regulated in 3AB group, 624 were expressed only in 3AB group, and 216 were expressed only in 3ABCon group in 3AB group. KEGG pathway analysis found that 83 pathways were up-regulated and 49 pathways were down-regulated, In GO analysis, 315 paths were up-regulated and 156 paths were down-regulated. There were 6 genes in the mab cluster that were only detected in the 3AB group.The mab cluster was found to be related to degradation of 3AB. By knockout, it was found that the growth rate of the mutant △ orf 7 and △ orf 9 were slowed down. HPLC results showed that the mutant △ orf 7 and △ orf 9 could still degrade 3AB, it was found that orf7 , orf9 were not key genes about 3AB degradation and they could be replaced by other genes in strain QT12. These findings improve our understanding of the molecular mechanisms underlying the cellular response of 3AB degradation in Comamonas bacterium.